The Critic of Sovereign State within "Lingkar Tanah Lingkar" Air Novel by Ahmad Tohari - Aji Royan Nugroho (Journal of Translation, Linguistics and Literature, 2024)
This research of Lingkar Tanah Lingkar Air aimed to investigated the position of state regarding Kafilah Darul Islam/Indonesian Islamic State (DI/TII) a goup that had been reducing towards sovereign power. Darul Islam appearance in that era was officially not avowed by the government, so they were losing their civil rights. Critic of Lingkar Tanah Lingkar Air Novel revealed that problem using Agamben political ideology in the relation between society and state. The research found that sovereign politic which used the state of exception to produce bare life under DI/TII group. Lingkar Tanah Lingkar Air gave a respond to the characters of the story. From the state of execption, they keep their effort with fellows to be able to defend anad raise their ideal life. The role of state should give the whole-secure and fair upon the DI/TII member, but with their sovereign; DI/TTI troop was homo sacred by the government becomes their official part